2013
DOI: 10.2298/pac1303123j
|View full text |Cite
|
Sign up to set email alerts
|

Natural radioactivity in imported ceramic tiles used in Serbia

Abstract: Ceramic tiles are one of the commonly used decorative building materials. Body of ceramic tiles is a mixture of different raw materials including clays, quartz materials and feldspat, and may be glazed or left unglazed. Due to the presence of zircon in the glaze, ceramic tiles can show natural radioactivity concentration significantly higher than the average values for building materials. This study presents a summary of results obtained by a survey which was consisted of measurements of acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…These results are relatively higher than the levels in previously investigated locally produced materials, particularly 238 U [21,22]. However, the activity concentrations of 238 U, 232 Th, and 40 K Bq/kg of ceramic samples in the present study are comparable, with slight variations with other studies in some countries [21,[23][24][25][26][27], as indicated in Table 2. Figure 1 shows a box-plot of 238 U, 232 Th, and 40 K activity concentrations, where the minimum, maximum, and means are presented.…”
Section: Radioactivity Contents In Ceramic Samplessupporting
confidence: 55%
See 1 more Smart Citation
“…These results are relatively higher than the levels in previously investigated locally produced materials, particularly 238 U [21,22]. However, the activity concentrations of 238 U, 232 Th, and 40 K Bq/kg of ceramic samples in the present study are comparable, with slight variations with other studies in some countries [21,[23][24][25][26][27], as indicated in Table 2. Figure 1 shows a box-plot of 238 U, 232 Th, and 40 K activity concentrations, where the minimum, maximum, and means are presented.…”
Section: Radioactivity Contents In Ceramic Samplessupporting
confidence: 55%
“…The range of computed H ex for ceramic samples was between 0.36 and 1.28, with a mean value of 0.74 ± 0.29 (Table 3). Interestingly, about 90% of the values are lower than unity, fitting well with the universal assigned value, showing that these materials are safe for building construction [7,25].…”
Section: The External Hazard Indexmentioning
confidence: 57%
“…Some what lower 40 K con cen tration val ues in this pa per, com pared to clays from the Ser bian mar ket, can be in ter preted by dif fer ent way of pre par ing a clayey ma te rial sam ple, or by mea sur ing a sam ple that has not un der gone in dus trial pro cess ing. Mea sured con cen tra tions of radionuclides in the sample of clayey ma te rial from the mine cor re spond to the val ues mea sured in the ce ramic tile as build ing ma terial [28]. Ar ti fi cial radionuclide 137 Cs was be low the de tec tion limit in all three clayey ma te rial sam ples (tab.…”
Section: Ac Tiv Ity Con Cen Tra Tions Of Radionuclides In Soil Sam Plesmentioning
confidence: 68%
“…In or der to val i date the re sults ob tained for spe cific ac tiv i ties, ac tiv ity con cen tra tion con ver sion was per formed: 238 U, 232 Th, and 40 K to mass con centra tions of ura nium, tho rium and po tas sium in soil [27,28]. The fol low ing val ues were ob tained: from 0.6 mgkg -1 to 5.7 mgkg -1 for ura nium (mean value 1.9 mgkg -1 ); from 4.4 mgkg -1 to 29.5 mgkg -1 for thorium (mean value 22 mgkg -1 ) and from 0.4 % to 2.4 % for po tas sium (mean value 1.2 %).…”
Section: Ac Tiv Ity Con Cen Tra Tions Of Radionuclides In Soil Sam Plesmentioning
confidence: 99%
“…Such activities would provide the useful data of doses and hazard indices to make them safe in houseware product (Ahmad et al, 2015;Papadopoulos et al, 2013). There are many numbers of work worldwide measured the natural radioactivity of ceramic and porcelain by gamma rays spectroscopy and used their values to determine the doses and the hazard indices, these data are important to human health and compare the results with the recommended limits (Aksoy et al, 2010;Tufail et al, 2010;Janković et al, 2013). The objectives of this study are: 1) Use X-Ray Diffraction and Atomic Absorption techniques to study the Chemical, Mineral, Compositions and Concentrations (of Some Metals) in fifteen local and imported Ceramic and Porcelain dinner wares samples.…”
Section: Introductionmentioning
confidence: 99%